ReKOMendacje PostępowAnia w mukowiScydozie (cystic fibrosis; CF) dla lekarzy Podstawowej Opieki Zdrowotnej - KOMPAS CF - część 1* - Sands, Dorota; Walicka-Serzysko, Katarzyna; Doniec, Zbigniew; Mastalerz-Migas, Agnieszka; Batura-Gabryel, Halina; Pierzchała, Władysław (Pediatria Polska - Polish Journal of Paediatrics, 2017)
In recent years, enormous progress has been made in the diagnosis and treatment of cystic fibrosis, which is no longer considered a fatal disease of childhood, rather it is referred to as a life shortening disease. The introduction of newborn screening for cystic fibrosis in Poland has made it possible to recognize the disease often before the onset of clinical symptoms. As a consequence of genetic screening development, new CFTR mutations previously undetected are now reported. However, we are yet to unravel how mutations will manifest, consequently it is necessary to isolate this new group of patients:CFSPID (Screened Positive Patients with Hypertrypsinogenemia and an inconclusive Diagnosis) for further observation.Cystic fibrosis patients require a comprehensive (which represents best practice),coordinated care delivered by a multidisciplinary team.Only such a model of care can markedly increase the mean survival of patients and improve their quality of life.A breakthrough in the treatment of cystic fibrosis is the introduction of new biological drugs that act causally inpatients with a specific genotype. In the future,this may lead to individualized treatment and will change the course of the disease.